Are Linguistic Responses Similar in Adult Literacy Students and Third-Fifth Grade Children? - Daphne Greenberg (Adult Education Research Conference, 2001)
This roundtable discussion will focus on a study of adult learners and children who recognize words at the third-fifth grade levels. Their responses to different linguistic task items will be compared and analyzed. Theoretical and instructional implications will be discussed.